DESAIN PEMBINAAN KARAKTER TERPADU - Sadrakh Sugiono; Jannes Eduard Sirait; Shirley D. Lasut; Channel Eldad (Bethel Press, 2021)
This study aims to formulate an Integrated Character Development Design through a constructive library research approach by analyzing theoretical literature, national education policies, and empirical studies on character education practices in schools. The findings indicate that character education in Indonesia is strongly supported by the Character Education Strengthening (PPK) policy and the 2013 Curriculum; however, its implementation still faces challenges in integrating character values across all subjects, limited teacher competence, and difficulties in assessing students’ attitudes. The proposed model consists of three key components: (1) planning, by integrating character values into the curriculum and teaching plans; (2) implementation, emphasizing teachers’ role as role models, habituation, and reinforcement through co-curricular and extracurricular activities; and (3) evaluation, focusing on continuous assessment of students’ behavior and the overall school culture. This model is expected to serve as an adaptive guide for schools to integrate character education comprehensively and contextually.